Visible-light driven photocatalytic oxygen evolution reaction from new poly(phenylene cyanovinylenes). (August 2017) - Mansha, Muhammad; Khan, Ibrahim; Ullah, Nisar; Qurashi, Ahsanulhaq; Sohail, Manzar
Abstract: Two new n-type conjugated polymers, poly( N -(2-ethylhexyl)-3, 6-carbazole- p -bis(2-ethylhexyloxy)-phenylene cyanovinylene) (P1 ) and poly( N -(2-ethylhexyl)-3, 6-carbazole- p -bisdodecyloxy-phenylene cyanovinylene) (P2 ) were synthesized and explored for their photo-electrochemical catalytic activity for oxygen evolution reaction (OER). When these polymers were used as photoanodes under visible light irradiation, oxygen evolution occurred at over potential as low as +0.6 V vs. SCE. In the chronoamperometric (CA) measurements, the photo-current density generated at +0.6 V byP1 andP2 was 0.31 and 0.27 μA/cm2, respectively. This is an excellent performance of a metal free and without the use of sacrificial electron donors polymer photoanodes. The higher photoelectrochemical (PEC) performance ofP1 was attributed to its narrow band gap and larger surface area. Moreover, the drastic quenching of the photoluminescence (PL) emission intensity ofP1 suggested the recombination of charges was effectively suppressed, which is in excellent agreement with our experimental observations. In the linear sweep voltammetry (LSV) measurements, the onset potential was observed at around 0.73 V whereas the maximum current densities byP1 andP2 were realized at 0.39 mA/cm 2 and 0.15 mA/cm 2, respectively. Long-term stability testing via CA indicated thatP1 was more stable thanP2, which warranted its potential as photocatalyst for solar water splitting. In addition, the optical band gaps ofP1 andP2, derived from the onset absorption edge, were found to be 2.51 and 2.62 eV, respectively, and the band gaps measured by Kubelka−Munk (KM), cyclic voltammetry (CV) and computational methods were found to be consistent. These polymers are readily soluble in common organic solvents which make them potential candidates for photovoltaic devices application. Highlights: Synthesis two new carbazole-containing polymers, P1 andP2, and evaluation of their PEC performance for OER. Characterized by 1 H-NMR, FTIR, DR UV-vis, SEM and TGA. Calculation of optical band gaps from % R vs. nm as well as by KM, CV and computational methods. The photo-current density generated byP1 andP2 was 0.31 and 0.27 µA/cm 2, respectively. The enhanced performance ofP1 was attributed to its narrow band gap and the larger surface area. No use of additional noble metal based cocatalysts or sacrificial electron donors.